Heuristic Algorithm for Portfolio Selection with Minimum Transaction Lots - ., Afnaria (Universitas Islam Sumatera Utara, 2013)
ABSTRACTPortfolio selection problem was first formulated in a paper written by Markowitz, where investment diversification can be translated into computing. Mean-variance model he introducedhas been used and developed because of itâs limitations in the larger constraints found in the realworld, as well as itâs computational complexity which found when it used in large-scale portfolio.Quadratic programming model complexity given by Markowitz has been overcome with thedevelopment of the algorithm research. They introduce a linear risk function which solve theportfolio selection problem with real constraints, i.e. minimum transaction lots. With the MixedInteger Linear models, proposed a new heuristic algorithm that starts from the solution of therelaxation problems which allow finding close-to-optimal solutions. This algorithm is built onMixed Integer Linear Programming (MILP) which formulated using nearest integer searchmethod. Key words: MILP, heuristics, portfolio optimization, minimum transaction lots, nearest integersearch.